Association of Oxidative Stress to the Genesis of Anxiety: Implications for Possible Therapeutic Interventions - Hassan, Waseem; Eduardo Barroso Silva, Carlos; Mohammadzai, Imdad Ullah; Batista Teixeira da Rocha, Joao; Landeira-Fernandez, J. (Current Neuropharmacology, 2014)
Oxidative stress caused by reactive species, including reactive oxygen species, reactive nitrogen species, and unbound, adventitious metal ions (e.g., iron [Fe] and copper [Cu]), is an underlying cause of various neurodegenerative diseases. These reactive species are an inevitable by-product of cellular respiration or other metabolic processes that may cause the oxidation of lipids, nucleic acids, and proteins. Oxidative stress has recently been implicated in depression and anxiety-related disorders. Furthermore, the manifestation of anxiety in numerous psychiatric disorders, such as generalized anxiety disorder, depressive disorder, panic disorder, phobia, obsessive-compulsive disorder, and posttraumatic stress disorder, highlights the importance of studying the underlying biology of these disorders to gain a better understanding of the disease and to identify common biomarkers for these disorders. Most recently, the expression of glutathione reductase 1 and glyoxalase 1, which are genes involved in antioxidative metabolism, were reported to be correlated with anxietyrelated phenotypes. This review focuses on direct and indirect evidence of the potential involvement of oxidative stress in the genesis of anxiety and discusses different opinions that exist in this field. Antioxidant therapeutic strategies are also discussed, highlighting the importance of oxidative stress in the etiology, incidence, progression, and prevention of psychiatric disorders.
Keywords: anxiety disorders